DIGITAL EARTH AS NEXT STEP IN CARTOGRAPHY - Eugene Eremchenko; Svemir Gorin; Vladimir Sergeevich Tikunov; Ivan Radevski (Geobalcanica, 2017)
Emerging of Google Earth in 2005 was perceived as significant achievements in geospatial sciences and bring into focus of mass attention the concept of Digital Earth, manifested seven years before by ex-vice-president of USA Al Gore. Nevertheless, scientific origins of Digital Earth and its relations with cartography still unclear. We investigate both problems and propose the vison of Digital Earth as a quantum leap in cartography method, or scientific revolution in the terms of Thomas Kuhn. Proposed vision of Digital Earth and extended classification of cartography methods, as well as its interdisciplinary impact, are explained and discussed (PDF) DIGITAL EARTH AS NEXT STEP IN CARTOGRAPHY. Available from: https://www.researchgate.net/publication/318350228_DIGITAL_EARTH_AS_NEXT_STEP_IN_CARTOGRAPHY [accessed May 23 2021].
Keywords: Digital Earth, Google Earth, Google Maps, cartography, decision making, situation awareness, sustainable development, neogeography, virtual geographic environments, holography. (PDF) DIGITAL EARTH AS NEXT STEP IN CARTOGRAPHY. Available from: https://www.researchgate.net/publication/318350228_DIGITAL_EARTH_AS_NEXT_STEP_IN_CARTOGRAPHY [accessed May 23 2021].